The status quo of Malaysian printmaking / Siti Safura Zahari...[et.al] - Zahari, Siti Safura; Roslan, Nur Fatiyah; Makrai, Nurin Elani; Karimon, Nor Arseha; Arshad, Mohd Fawazie; Mahmud, Romli (2016)
In Malaysia, Printmaking is not a highly popular art discipline. It has failed to receive the attention that it rightly deserves and is mainly overshadowed by the more popular art disciplines such as painting and sculpture. This is due to the perception that printmaking is insignificant compared to other branches of art during the early development period of Malaysia contemporary art. This study was conducted to identify the key factors on why printmaking in Malaysia is not fully developed. There are two important aspects on printmaking in Malaysia will be covered in this research. As we know, printmaking came into process in the late 1950s and its development continued until the 1990s. The first aspect to be discussed is the background of the study that highlights the printmaking history since Independence, and the questions on whether the development of printmaking after the 1990s have further developed and progressed or on the contrary. There is evidence that show a number of paintings being discovered in an exhibition held in 1958. However, there is no sign of printmaking in Malaysia back then. The study is expected to assist and benefit the printmakers and the enthusiasts of printmaking as well as researchers in studying and finding effective solutions to help develop this discipline of art in the future.